Comparative approaches to biotechnology development and use in developed and emerging nations - Bas, Tomas Gabriel; Zhao, Jingyuan 1968- (IGI Global, Medical Information Science Reference, 2017)
"This book evaluates the importance of manufacturing biotechnological products around the world, highlighting a comparative analysis of public policies, technological policies, innovations, and marketing capability of developed and emerging nations"...
Includes bibliographical references and index
Keywords: Entwicklungsländer; Politik; Biotechnology -- Developing countries; Biotechnology -- Government policy -- Developed countries